Effects of nitrogen fertilization on the photosynthesis and biomass distribution in a potato crop - José E. Salas-Rosales (Universidad Nacional Agraria La Molina, 2020)
Nitrogen fertilization has positive effects on growth and production of potato crop. The objective of this study was to assess the differences of the photosynthetic response and biomass partitioning patterns during the main phenophases of the potato cultivar Capiro under different nitrogen nutrition fertilization treatments in the tropical Andes of Mérida, Venezuela. Plots of 40 m2 (2,625 plants m-2) were established under a random block design with three replications by nitrogen fertilization treatment: 0, 100, 200, and 300 kg. N ha-1. Photosynthesis and biomass were measured in the different organs in the main phenological stages of the crop. The results indicate that photosynthesis tends to increase slightly with the nitrogen supply; although the differences were not always significant and, decreases during crop growth. Tubers yield it was markedly influenced by the nitrogen fertilization. The total biomass production, as well as biomass allocation in different organs showed differences between treatments, maintaining the following order: 300-N> 200-N> 100-N> 0-N. When analyzing the biomass accumulation curves, it is estimated that the application of 250 kg N ha-1 as mineral fertilizer is enough to reach optimal production yields.